THE SECONDARY AND HIGH SCHOOL STUDENTS' BOREDOM IN LEARNING ENGLISH - Ferdiansah, Deny; Hartono, Rodi; Pranata, Ogi Danika (Universitas Muhammadiyah Metro, 2024)
Academic boredom is a primary emotion that negatively impacts learners' engagement, including in English classes at school. This study employed a descriptive and comparative quantitative approach to explore engagement levels in practical English classes among 76 secondary and high school students in Kerinci, Jambi, Indonesia. An adapted questionnaire was distributed via Google Forms through WhatsApp groups, and the collected data were analyzed using descriptive and comparative statistics. The results indicate that students experience the highest levels of boredom in class-related aspects (2.33), followed by boredom proneness (2.28) and study-related aspects (2.12). Both middle and high school students learning English had significant boredom levels. The boredom proneness (P) aspect, particularly P4, revealed a notable difference between these groups.In contrast, the class-related (C) and study-related (S) aspects showed no significant differences. The Academic Boredom Survey Instrument proved to be a valuable tool for assessing student engagement, particularly in the context of academic boredom research. These findings offer educators insights into tailoring teaching methods and curricula to mitigate academic boredom among secondary and high school students.